2004
DOI: 10.1038/sj.bmt.1704539
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase 2 trial of stem cell transplantation for immunoglobulin light-chain amyloidosis (E4A97): an Eastern Cooperative Oncology Group Study

Abstract: Summary:Stem cell transplantation was introduced as a new therapeutic modality for amyloidosis. The purpose of the current study was to determine the feasibility and toxicity of stem cell transplantation for amyloidosis in a cooperative group setting in which most participating institutions would have limited experience in managing the disorder. A total of 30 patients with biopsy-proven amyloidosis shown to be immunoglobulin light-chain type were enrolled on this trial. The protocol required mobilization of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 40 publications
2
22
0
2
Order By: Relevance
“…6 Single and multicenter studies show CR rates of 16%-67%, organ responses in 25%-45% of patients, and a median overall survival (OS) of ϳ 5 years. [7][8][9][10][11][12][13][14][15][16] A case-control study demonstrated the benefit of this procedure for patients younger than 70 years compared with nontransplant regimens, most of them alkylator-based oral chemotherapy. 17 A major issue in HDM/SCT for AL amyloidosis is the potential for high treatment-related mortality (TRM) because of underlying organ dysfunction in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…6 Single and multicenter studies show CR rates of 16%-67%, organ responses in 25%-45% of patients, and a median overall survival (OS) of ϳ 5 years. [7][8][9][10][11][12][13][14][15][16] A case-control study demonstrated the benefit of this procedure for patients younger than 70 years compared with nontransplant regimens, most of them alkylator-based oral chemotherapy. 17 A major issue in HDM/SCT for AL amyloidosis is the potential for high treatment-related mortality (TRM) because of underlying organ dysfunction in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Intravenous administration of high dose melphalan (HDM) supported by autologous stem cell transplantation (ASCT) significantly increased the hematologic and organ responses and improved survival, but at the expense of a treatment-related mortality rate ranging between 14% and 43% depending on the severity of the heart involvement and number of organs affected. [6][7][8][9][10][11][12][13][14][15] A risk-adapted approach has been attempted to adjust the dose of melphalan according to the patient's age and organ involvement; 12,16 with this approach early mortality is reduced but the response rate appears to be lower. 12,17 Another important advance in the treatment of AL amyloidosis was the observation that a modified schedule of high dose dexamethasone was effective in many patients with this disease.…”
mentioning
confidence: 99%
“…(For example, a phase II multicenter SCT trial conducted in the United States had no patients fail to get to SCT and a 10% treatmentrelated mortality [41].) Additional problems include the fact that the response rate of oral melphalan and dexamethasone was unknown at the time the French trial was designed.…”
Section: Table 1 Guidelines For the Use Of Melphalan And Sct In A Rimentioning
confidence: 97%